Aji Saka: Pahlawan, Legenda, dan Warisannya dalam Kebudayaan Jawa - Aprilia, Putri; Jumadi, Jumadi; Wahyu, Dwi; Dewi, Candra (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article discusses legendary figures on the island of Java who have been passed down from generation to generation. Aji Saka comes from Majethi, India. Aji Saka is known as the creator of the Javanese script and the Saka calendar or Javanese calendar. Through a literature review approach, this research aims to collect and analyze the story of Aji Saka from various sources that have been documented, such as his origins, his fight against Prabu Dewata Cengkar, his influence on Javanese culture, the history of the creation of the Javanese script and the Saka calendar which is still relevant in society today. Apart from analyzing it from a historical perspective, this research will also discuss the symbolic meaning and moral values of Aji Saka's story which can be a role model. Thus, it can be said that Aji Saka is not only a legendary figure but also an integral part of history and cultural identity which is still preserved today.